Pre-service Teachers’ Perceptions of Canva’s Effectiveness in Supporting Different Learning Styles in English Language Teaching - Alya Syaharani Handini; Putu Dian Danayanti Degeng (Journal of Education and Teaching Learning, 2026)
This study examines pre-service teachers’ perceptions of Canva’s effectiveness in supporting different learning styles in English Language Teaching (ELT). It explores how Canva facilitates visual, auditory, and kinesthetic approaches, as well as the challenges faced in developing instructional materials. Using a quantitative descriptive design, the study involved 60 pre-service English teachers from State University of Malang and Brawijaya University who had prior experience using Canva. Data were collected through a structured Likert-scale questionnaire distributed via Google Forms and analyzed using descriptive statistics such as mean and standard deviation with IBM SPSS Statistics 25. Findings indicate that Canva is highly effective in supporting especially visual and kinesthetic learning, as shown by very high mean scores. Despite some challenges in its use for instructional material development, Canva positively contributes to teaching presence, cognitive presence, and social presence in the classroom. The study concludes that Canva is a useful platform for creating instructional materials that accommodate diverse learning styles in English language teaching.